Modeling of the spontaneous polypropylene sorbents imbibition with emulsions - Sęk, Jerzy; S. Shtyka, Olga; Szymczak, Kamila (Journal of Environmental Engineering and Landscape Management, 2015)
Oil penetration into aqueous media results in various chemical and physical processes including formation of “oil-in-water” emulsions, that have devastating effects on the environment. This research was conducted to evaluate the kinetics of permeation of “oil-in-water” emulsions into synthetic porous material. It gives the ability to develop more effective sorbents, decreasing risks of negative consequences and environmental contamination. The following publication focuses on assessment of the possibility to describe and predict a process of porous medium imbibition with emulsions by means of the Hill equation. Its adequacy is compared with the classical Lucas–Washburn equation and its modified version. The advanced approach is to substitute the commonly used parameter of the height of an imbibed emulsion (h(t)) by the parameter mh(t), which is the mass of an imbibed emulsion in the case of the classical and modified Washburn equations. According to the obtained results, the Hill equation provides the most appropriate and precise description of the porous material imbibition with “oil-in-water” emulsions and oil in comparison with others, and shows the highest correlation values (Rav = 0.995±0.001) and the lowest normalized root mean square error (NRMSEav 1.95±0.138). First published online: 13 Dec 2014